Effect of giving ethanol multistep doses to level of SGPT and SGOT in wistar rats (Rattus norvegicus) - Istiqomah Kurniawati; Titis Nurmasitoh; Taufik Nur Yahya (Faculty of Medicine, Universitas Islam Indonesia, 2015)
Background: Ethanol is one types of alcohol used in beverages. Excessive use of ethanol causes damage to organs, especially in the liver. Liver, which is an organ in the body, serves as the metabolism of various substances including ethanol. Liver damage that occurs can be known with one of these liver function examination, which check the levels of SGPT and SGOT.Objective: This research aims to look for the difference of SGPT’s and SGOT’s levels between ethanol multistep doses group and control group in Wistar rats (Rattus norvegicus) SGPT and SGOT levels.Methods: This study used an experimental research design with post test only control group design. The sample consisted of 21 male Wistar rats, which were divided into 3 groups. Each group consisted of 7 rats. The first group (K1) was the control group, which was given aquades. The second group (K2) were given ethanol 20% as 2 g/kg pe roral. And the third group (K3) were given with 25% ethanol as 2.5g/kg peroral. The treatment was given for 4 weeks. At the 31st day blood was taken from orbitalis sinus as much as 1 ml for check the level of SGPT and SGOT.Results: The results are the average increase of SGPT and SGOT levels in K2 compared to the K1. While on K3 showed that the average levels of SGPT and SGOT were lower than K1. SGPT levels showed a significant difference (p0.05 ). Conclusion: There is significant differences in the levels of SGPT treatment group in comparison with the control group, but there is no significant differences in the level of SGOT.